2016
DOI: 10.1186/s40510-016-0144-y
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of root dimensions and alveolar ridge width of maxillary lateral incisors in patients with unilateral agenesis

Abstract: BackgroundThe objective of this retrospective case-control study was to measure the maxillary lateral incisor root dimensions and quantify the labial and palatal bone in patients with unilateral maxillary lateral incisor agenesis (MLIA) after orthodontic treatment and compare them to non-agenesis controls using cone beam computed tomography.MethodsThe labiopalatal and mesiodistal root dimensions, mesiodistal coronal dimensions, and labiopalatal bone and alveolar ridge widths of the maxillary lateral incisor we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Only few studies have been published on the different types of bone abnormalities resulting from dental agenesis (AlRushaid et al, 2016;Romieux et al, 2000;Uribe et al, 2013). First, Romieux et al, 2000 described abnormalities in the anterior part of the mandible, where they observed a blade shape without height loss, whereas in the posterior part, the distance between the crest rim and the dental canal was preserved.…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have been published on the different types of bone abnormalities resulting from dental agenesis (AlRushaid et al, 2016;Romieux et al, 2000;Uribe et al, 2013). First, Romieux et al, 2000 described abnormalities in the anterior part of the mandible, where they observed a blade shape without height loss, whereas in the posterior part, the distance between the crest rim and the dental canal was preserved.…”
Section: Introductionmentioning
confidence: 99%
“…Farhat et al, in his study have stated that, the average mesiodistal width of maxillary lateral incisors is 6.5 mm. They are usually 2 mm longer mesio distally and 2 mm shorter cervico incisally than that of canine and central incisors (AlRushaid et al, 2016). Peg shaped lateral incisors are considered as the variable expression of the gene responsible for congenitally missing maxillary lateral incisors (Alvesalo and Portin, 1969;Arte et al, 2001).…”
Section: Introductionmentioning
confidence: 99%